2016
DOI: 10.1111/pcn.12460
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement as a biomarker of schizophrenia: Using an integrated eye movement score

Abstract: Aim: Studies have shown that eye movement abnormalities are possible neurophysiological biomarkers for schizophrenia. The aim of this study was to investigate the utility of eye movement abnormalities in identifying patients with schizophrenia from healthy controls.Methods: Eighty-five patients with schizophrenia and 252 healthy controls participated in this study. Eye movement measures were collected from free viewing, fixation stability, and smooth pursuit tests. In an objective and stepwise method, eye move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
115
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 71 publications
(122 citation statements)
references
References 22 publications
(60 reference statements)
6
115
0
1
Order By: Relevance
“…Many endophenotypes, such as eye‐movement characteristics and brain structural changes, are known in schizophrenia (SCZ). Eye movements serve as an output of cognitive processing and better performance has been associated with better social functioning in SCZ .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many endophenotypes, such as eye‐movement characteristics and brain structural changes, are known in schizophrenia (SCZ). Eye movements serve as an output of cognitive processing and better performance has been associated with better social functioning in SCZ .…”
mentioning
confidence: 99%
“…Data of 102 participants with SCZ and 341 healthy controls were analyzed (Table S1). We focused on three eye‐movement measures (scanpath length, horizontal position gain, and duration of fixations) and a score integrating these three measures . The respective associations between these measures and the cortical thickness of 34 bilateral regions based on the Desikan–Killiany atlas were tested.…”
mentioning
confidence: 99%
“…One important factor concerning schizophrenia is the effect of antipsychotic agents . The effect of dopamine blockade associated with antipsychotic agents is known to affect muscle movements, causing extrapyramidal symptoms such as parkinsonism, dystonia, and dyskinesia.…”
Section: Resultsmentioning
confidence: 99%
“…Discovery of disease‐specific biomarkers or behavioral indicators with sufficient sensitivity is an important issue to improve the clinical diagnosis of mental illness. Magnetic resonance images, near‐infrared spectroscopy, genetic markers, cognitive functions, and eye movements are candidates . Of them, eye movement is representative of sensorimotor functions of the brain, and eye movement abnormalities have been reported in subjects with schizophrenia .…”
Section: Introductionmentioning
confidence: 99%
“…Of them, eye movement is representative of sensorimotor functions of the brain, and eye movement abnormalities have been reported in subjects with schizophrenia . It has been frequently reported that subjects with schizophrenia can be successfully distinguished from healthy individuals by using eye movements . However, it is unknown whether the eye movement abnormalities that distinguish subjects with schizophrenia from healthy individuals are also effective in discrimination from other psychiatric disorders, such as autism spectrum disorder (ASD), which is a neurodevelopmental condition in which affected individuals have difficulties in social interactions and communications .…”
Section: Introductionmentioning
confidence: 99%